BER Performance Analysis on AWGN Channel and Fading Channel by Using Diversity Method - Waluyo, Catur Budi (Sekolah Tinggi Teknologi Adisutjipto, 2018)
In the last decades the development of telecommunications technology has increased. In the network access, one of the factors that influences was multipath fading. This study was aimed to simulate the effect of noise on digital communication error detection for various combinations of Eb / No, as well as simulating the effect of various diversity techniques on BER values. In this study the performance of the wireless network communication system was measured in bit error rate (BER) as a function of the ratio of bit energy to noise power. Result of simulation from AWGN channels obtained BER values at Eb / No are 2dB, 4dB, 6dB and 8dB, respectively 4 x 10-2, 1.2 x 10-2, 2.2 x 10-3 and 2 x 10-4. The BER results on fading channels using spatial diversity were better than BER on fading channels without any use of antenna diversity with a difference of 10dB.